Bimetallic Rh–Fe catalysts for N2O decomposition: effects of surface structures on catalytic activity. Issue 7 (2nd February 2018) - Chen, Hao; Lu, Qinghua; Yi, Chunhai; Yang, Bolun; Qi, Suitao
Abstract : Well-homogenized RhFe alloy nanoparticles and core–shell structured Fe@Rh nanoparticles were highly dispersed on SBA-15 and then applied to N2 O catalytic conversion. Abstract : Well-homogenized RhFe alloy nanoparticles and core–shell structured Fe@Rh nanoparticles were highly dispersed on SBA-15 and then applied to N2 O catalytic conversion. Compared to RhFe/SBA-15, Fe@Rh/SBA-15 showed a higher catalytic activity for N2 O decomposition. This is because the Rh layers covering the Fe core were able to protect against oxidization and so Fe@Rh/SBA-15 was prevented from deactivating. DFT calculations were performed to study the reaction mechanism of N2 O decomposition. The rate-determining step, which was found to be the formation of O2 from adsorbed oxygen atoms on the surfaces of RhFe and Fe@Rh, revealed that O atoms prefer to be adsorbed on exposed Fe atoms on the surface of RhFe rather than that of Fe@Rh. The calculation results indicate that the exposed Fe atoms tend to be oxidized on the surface of RhFe, resulting in the deactivation of RhFe/SBA-15 during the experiment.